PENGARUH MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE TERHADAP PEMBELAJARAN PASSING SEPAK BOLA - Bardiono Bardiono; Andika Triansyah; Uray Gustian (Universitas Tanjungpura, 2019)
AbstractThe research problem is whether there is an influence of the cooperative laerning model type of think pair share on learning the basic techniques of passing football. The purpose of this study,